Circular RNA expression profiles following negative pressure wound therapy in burn wounds with experimental Pseudomonas aeruginosa infection. Issue 2 (1st February 2022) - Yang, Yunshu; Liu, Mengdong; Yang, Fangfang; Wang, Xujie; Bai, Xiaozhi; Mu, Shengzhi; Liu, Yang; Hu, Dahai
ABSTRACT: Infections of burn wounds, especially those caused by Pseudomonas aeruginosa, could trigger sepsis or septic shock, which is the main cause of death after burn injury. Compared with traditional saline-wet-to-dry dressings, negative pressure wound therapy (NPWT) is more effective for the prevention and treatment of wound infections. However, the mechanism by which NPWT controls infection and accelerates wound healing remains unclear. Accordingly, in this study, the molecular mechanisms underlying the effects of NPWT were explored using a murine model of P. aeruginosa -infected burn wounds. NPWT significantly reduced P. aeruginosa levels in wounds, enhanced blood flow, and promoted wound healing. Additionally, NPWT markedly alleviated wound inflammation and increased the expression of wound healing–related molecules. Recent evidence points to a role of circular RNAs (circRNAs) in wound healing; hence, whole-transcriptome sequencing of wound tissues from NPWT and control groups was performed to evaluate circRNA expression profiles. In total, 12 up-regulated and 25 down-regulated circRNAs were identified between groups. Among these, five significant differentially expressed circRNAs acting as microRNA sponges were identified, and their predicted targets were verified by reverse transcription-quantitative polymerase chain reaction. These results further support the roles of circRNAs in wound healing by NPWT and the prevention of P. aeruginosa infection, providing key molecular targets for further functional analyses.